Character Based Text for Development on V Grade Students of Elementary School - Burhanuddin Habibi Nasution; Abdul Rahman; Syahnan Daulay (Indonesian Language and Literature Education Study Program and LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2019)
Amrullah, I., Imayah. (2019). Building students’ characters through character education and religiousity values in Syair Kitab Ta'lim Muta'allim. Jurnal AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 3(1), 53—65. doi: https://doi.org/10.21009/AKSIS.030106 Cohen, T.R., & Morse, L. (2014). Moral character: What it is and what it does. In A.P. Brief & B.M. Staw (Eds.), Research in Organizational Behavior. Elsevier. Retrieved from https://www.researchgate.net/publication/264000952_Moral_character_What_it_is_and_what_it_does Danandjaja, J. (1999). Folklor Indonesia, Ilmu Gosip, Dongeng, dan Lain-Lain. Jakarta: Grafiti. Dani, E.D. (2013). Pembentukan karakter anak melalui kegiatan mendongeng. .Jurnal Humanika, 17(1), 91—124. doi: 10.14710/humanika.17.1 Effendi, R. (2017, May 10). Hukum berat pembunuh keponakanku. Waspada, p. 5. Klein-Ezell, C., Ezell, D., Stanley, S.P., & Powell, S.E. (2014). Character education using children’s literature, puppets, magic tricks and balloon art. International Journal of Humanities and Social Science, 4(14), 1—15. Lickona, T. (2012). Character Matters. Jakarta: Bumi Aksara. Muslich, M. (2011). Pendidikan Karakter Menjawab Tantangan Krisis Multidimensional. Jakarta: Bumi Aksara. Purwahida, R. (2017). Interaksi sosial pada kumpulan cerpen Potongan Cerita di Kartu Pos karangan Agus Noor dan implikasinya terhadap pembelajaran sastra di SMA. Aksis: Jurnal Pendidikan Bahasa dan Sastra Indonesia 1(1). 118-134. doi: doi.org/10.21009/AKSIS.010107 Purwahida, R. (2018). Problematika Pengembangan Modul Pembelajaran Baca Tulis Anak Usia Sekolah Dasar. Aksis: Jurnal Pendidikan Bahasa dan Sastra Indonesia 2(1). 118-134. doi: doi.org/10.21009/AKSIS.020108. Sibarani, R. (2012). Local Wisdom: Hakikat, Peran, dan Metode Tradisi. Jakarta: ATL. Sugiyono. (2014). Metode Penelitian dan Pengembangan (Research and Depelopment: R&D). Bandung: Alfabeta. Sukmawan, S. (2016). Ekokritik Sastra: Menanggap Sasmita Arcadia. Malang: Universitas Brawijaya Press. Sulistyawati, Sri, Risnawaty, & Purba, N. (2015). Model pembentukan karakter bangsa terhadap siswa SMA dalam mengantisipasi pencegahan tindak pidana korupsi di Sumatera Utara. Laporan Penelitian Tahap I: Unggulan Perguruan Tinggi. Medan: UMN Al Washliyah. Syaifuddin, W. (2016). Pemikiran Kreatif & Sastra Melayu Tradisi. Yogyakarta: Gading. Turan, F., & Ulutas, I. (2016). Using storybooks as character education tools. Journal of Education and Practice, 7(15), 169—176. Wardani, Y. F. & Suhita, S. (2018). Nilai Pendidikan Karakter dalam Novel Rindu Karangan Tere Liye: Tinjauan Psikologi Karakter. Aksis: Jurnal Pendidikan Bahasa dan Sastra Indonesia 2(2). 247-273. doi: doi.org/10.21009/AKSIS.020207